Membongkar Agensi Objek dalam Produksi Craft Menuju Pembangunan Berkelanjutan - Werdhaningsih, Hendriana (Jurnal Desain Indonesia., 2025)
Sustainable development (SD) is a global agenda that needs multi stakeholders participation to ensure it reaches the goals, including craft and design practitioners intervention. It shall begin with understanding what a certain kind of sustainability means at the practical level. Learning that traditional craft practice reflects the SD principles and the significance of objects as agencies, this paper unpack the kinds of objects in craft production and its agency endorse sustainable development principles. It used multiple sources within one research design by triangulating the data from multiple data collection methods: designer interviews; field research in a bamboo craft production in Tasikmalaya (Indonesia); and in a glassblowing workshop in Chicago (North America). The result shows that objects, such as material, tools, and space contribute to the harmony of social, environmental, and economic systems. Objects ‘kick back’ formulates production constraints in material sourcing and treatment, and capacity of production. It facilitates social capital that strengthens the social system in the community, and shapes craft production to focus on well-being instead of great income. Object agencies in craft production could inspire design intervention in sustainable development.